The effectiveness of remote delivered intervention for loneliness reduction in older adults: A systematic review and meta-analysis - Fu, Zhengke; Yan, Mengsi; Meng, Chao (Frontiers in Psychology, 2022)
Background Remotely delivered intervention is widely applied to loneliness treatment in older adults, but the effect is controversial. This study aimed to evaluate the effects of remotely delivered intervention on loneliness using a systematic review and meta-analysis. Methods The PubMed, the Cochrane Central Register of Controlled Trials, EMBASE, CINAHL (EBSCO), PsycINFO (EBSCO) databases were searched for studies, the search ended on 7 July 2021. Thirteen randomized controlled trials of remotely delivered intervention compared with usual care, brief contact, or no intervention for loneliness were included. A random-effects model measured estimation of loneliness reduction. Furthermore, standardized mean differences (SMDs), 95% confidence intervals (CIs), publication bias, and heterogeneity were calculated. Subgroup analysis was used to explore the factors that might affect the treatment effects. Results The evidence of remotely delivered intervention on loneliness reduction was certain (SMD = −0.41 [95% CI, −0.70 to −0.13]). Media subgroup analysis supported the effectiveness of intervention delivered by video call (SMD = −0.54 [95% CI, −0.83 to −0.25]); treatment strategy subgroup analysis found evidence to support the effectiveness of increasing social support and maladaptive social cognition treatment strategy (SMD = −0.47 [95% CI, −0.77 to −0.18] and SMD = −1.04 [95% CI, −1.98 to −0.10], respectively); participants subgroup analysis shown the effectiveness of intervention for older adults living in LTC and social isolation (SMD = −1.40 [95% CI, −2.43 to −0.36] and SMD = −0.55 [95% CI, −0.74 to −0.36], respectively); group format subgroup analysis testified the effectiveness of intervention carried out in individual format (SMD = −0.39 [95% CI, −0.71 to −0.07]); measurement time points subgroup analysis found the positive effect of intervention at 3 months and 3 to 6 months stage (SMD = −0.33 [95% CI, −0.52 to −0.14] and SMD = −0.32 [95% CI, −0.57 to −0.07], respectively). Significant publication bias was detected (p < 0.05), and the heterogeneity of the studies was substantial. Conclusion This systematic review and meta-analysis demonstrate that remotely delivered intervention can reduce loneliness in older adults, and it appears to be affected by media type, treatment strategy, participants characteristics, group format, and measurement time points.